La adquisición/aprendizaje de la pronunciación, del vocabulario y de las estructuras interrogativas en lengua inglesa. Un estudio por edades - Moya Guijarro, Arsenio Jesús (Didáctica. Lengua y Literatura, 2003)
The aim of this article is to determine the fundamental differences that exist, as far as pronunciation, vocabulary and interrogative structures are concerned, in the process of learning/ acquisition of English as a mother tongue and as a foreign language in the early years. In the light of the empirical study carried out, I can confirm the existence of a similar developmental process in the learning / acquisition of pronunciation, lexical items and interrogative structures in both contexts.